The Crime Of Damage After the Constitutional Court's Decision Number 76/PUU-XV/2017 - Abdul Kadir Jaelani; Resti Dian Luthviati (Lembaga Contrarius Indonesia, 2021)
From 2009 until now, there have been 30 cases tried by the Court with the use of Article 27 paragraph (3) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. These various cases have raised opinions from some people who consider defamation offenses contrary to the spirit of reform that upholds freedom of thought and expression. Crime of reputation after the Constitutional Court Decision Number 50/PUU-VI/2008, Constitutional Court Decision Number 2/PUU-VII/2009, Constitutional Court Decision Number 5/PUU-VIII/2010, Constitutional Court Decision Number 31/PUU-XIII/ 2015, and the Decision of the Constitutional Court Number 76/PUU-XV/2017 concerning the Review of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 regarding Information and Electronic Transactions against the 1945 Constitution of the Republic of Indonesia are regulated in detail with one of the points, namely making changes in Article 27 paragraph (3) of the ITE Law and reducing criminal threats in 2 (two) provisions. Keywords: Reputation Offenses; Legal Certainty; Constitutional Court.